Representation of Sexual Violence Survivors in Cinta Pertama Ayah Movie - Nadaa, Nadaa Santi Wulandari; Nurul Aisyah, Vinisa (Jogjakarta Communication Conference (JCC), 2025)
Lived experiences, trauma, stigma, and recovery are complex emotional and psychological issues which survivors of sexual violence deal with, which are often portrayed in the media including movies. This study aims to analyze how survivors of sexual violence are represented in the film Cinta Pertama Ayah. This study will identify and interpret the signs and symbols used in the film to depict survivors of sexual violence, exploring the emotional and psychological impacts experienced by the victims. The theory used is Roland Barthes' semiotic theory, which helps to explore signs and symbols in the narrative and key scenes that represent the traumatic experiences of survivors. This study is qualitative descriptive. The sampling technique applied is purposive sampling, with scene criteria (scenes, dialogues, settings) that depict survivors of sexual violence, sexual violence survivor characters. Data collection techniques in the form of observation are carried out by watching in depth scenes that present survivors of sexual violence, and data validity is tested using the triangulation method. Data analysis uses Barthes' semiotic model by identifying layers of denotative, connotative, and mythical meaning. The results of the study show that the meanings constructed by survivors of sexual violence in the film Cinta Pertama Ayah vary greatly, depending on the context and scenes shown. The film successfully depicts the traumatic experiences of survivors through visual and narrative signs and emphasizes the importance of emotional support from the surrounding environment in the recovery process.